Determination of a new collagen type I alpha 2 gene point mutation which causes a Gly640 Cys substitution in osteogenesis imperfecta and prenatal diagnosis by DNA hybridisation. Issue 12 (December 1994) - Gomez-Lira, M; Sangalli, A; Pignatti, P F; Digilio, M C; Giannotti, A; Carnevale, E; Mottes, M
Abstract : The molecular defect responsible for a sporadic case of extremely severe (type II/III) osteogenesis imperfecta was investigated. The mutation site was localised in the collagen type I pro alpha 2 mRNA molecules produced by the proband's skin fibroblasts by chemical cleavage of mismatch in heteroduplex nucleic acids. Reverse transcription-polymerase chain reaction DNA amplification, followed by cloning and sequencing, showed heterozygosity for a G to T transversion in the first nucleotide of exon 37 of the COL1A2 gene, which led to a cysteine for glycine substitution at position 640 of the triple helical domain. This newly characterised mutation is localised in a domain which contains several milder mutations, confirming that glycine substitutions within the alpha 2(I) chain do not follow a linear gradient pattern for genotype to phenotype correlations. In a subsequent pregnancy, absence of the G2327T mutation in the fetus was shown by allele specific oligonucleotide hybridisation to the trophoblast derived fibroblast mRNA after reverse transcription and in vitro amplification. (The nucleotide number assigned to the mutant base was inferred from the numbering system devised by the Osteogenesis Imperfecta Analysis Consortium (The OIAC Newsletter, 1 April 1994).)